Analisis Teks Berita Anak Berlabel Broken Home di Media Online - Adra Absyar; Mutia Rahmi Pratiwi (IQTIDA : Journal of Da'wah and Communication, 2022)
The continuity of family life is something that is expected to continue from the side of both parents and children. But in fact, the data shows that the number of divorces in Indonesia is increasing.Divorce has an impact on children in the position of victims and the emergence of the label of broken home children. Stigma in society shows that children from a broken home are often considered a source of problems in their environment. News about children from broken homes is an interesting thing to study regarding the role of the media in strengthening the existing stigma or vice versa. The purpose of this study is to dissect news texts in the Kompas.com media,explicitly reporting about broken home children using framing analysis methods. The number of news objects is 9 news texts that appear during the span of 2019-2020. The results showed that in reporting about broken home children, they focused more on delinquency from broken home children and considered it a painful experience for children. Of the 9 news that became the object of research, more than 90 percent told about the negative stigma of a broken home child. The reality that is built on the object of the news is to strengthen the negative stigma against children from broken homes. The research findings are the basis for the urgency of the role of parents in supervising children even though they are not in the form of a complete family.